Colombia - Assisting Talented Students from Low-income Families Attend Tertiary Education - Cerdán-Infantes, Pedro (World Bank, Washington, DC, 2012)
With the support of the ACCES (Acceso Con Calidad a la Educacion Superior, in Spanish) Project Colombia shifted its tertiary education policy, implementing comprehensive reforms to improve equity of tertiary education. The result of this shift has been impressive: enrollment in tertiary education increased by 30 percent in the last 3 years. The project has contributed to improved access to tertiary education for the poor through three direct outcomes: 1) the availability of student loans for low-income students was markedly improved by the project; 2) the support to doctoral programs has dramatically increased the number of Colombian doctoral students and programs; and 3) the institutional capacity of the Ministry of Education has increased substantially.